A Vehicle Routing Problem for Efficient Waste Transportation Using Ant Colony Algorithm: Marang Region - Kamarudin, Siti Fauziah; Jamaian, Siti Suhana (Enhanced Knowledge in Sciences and Technology, 2023)
Housing waste collection would be a very big problem if it is not handled properly. It will have a poor quality of life and causes individuals to suffer in their daily lives. Therefore, maintaining a clean environment in a pleasant way of life requires an effective garbage collection strategy. The aims of this research are to study a vehicle routing problem for efficient trash transportation specially related to household waste collection in Marang region. In this research, our objective is to obtain the optimal solution for the efficient trash transportation by minimizing the total distance and with a minimum cost. Since the vehicle routing problem is the NP-hard problem (nondeterministic polynomial time), the ant colony optimization (ACO) is used to solve the problem with the assist of Python. The latitude and longitude for the disposal center which is at Kampung Sungai Serai and 18 locations in Marang region were directly taken from the Global Positioning System (GPS). The locations are divided with two Zones which are 10 locations for Zone 1 and 8 locations for Zone 2. Since this study is focused on the housing waste collection, the occupied points taken are all in the residential area. The total distance of the route obtained was recorded in Kilometers. The result was run twenty- one times for Zone 1 and ten times for Zone 2 to determine the best solution for the vehicle routing which used the least total distance and minimum total cost. Finally, the results were obtained in five seconds with the assistance of Python. The eleventh result with the minimum total cost is RM29.08 and the shortest distance is 37.69 KM for Zone 1 and third result with the minimum total cost is RM16.94 and the shortest distance is 17.22 KM for Zone 2 are the optimal route solution.